EFEK PEMBERIAN EKSTRAK LIMBAH TEH HITAM SEBAGAI SUMBER ANTIOKSIDAN DAN LEVEL ENERGI â PROTEIN PAKAN YANG BERBEDA TERHADAP STABILITAS OKSIDATIF DAN KUALITAS DAGING AYAM BROILER - , DILLA MAREISTIA FASSAH, Dr. Ir. Supadmo, MS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study was purposed to determine the black tea waste extract effect as a source of antioxidants, the level of energy - protein rations as well as the interaction between them to oxidation stability and meat quality of broilers. The experiment used an analysis of variance factorial pattern 3 x 3 (3-level factors providing feed additives and 3 types of rations) and if there were significant differences, continued with Duncan Multiple Range Test (DMRT). Ration types namely Type 1: low energy â protein (CP 18,03% and ME 2769,41 kcal/kg), Type 2: medium energy â protein (CP 20,03% and ME 3013,54 kcal/kg), Type 3: high energy â protein (CP 22,09% and ME 3351,62 kcal/kg). Each ration treatment was given four levels of additives providing: black tea waste extract 0 mg/kg of feed, 500 mg/kg of feed and 1000 mg/kg of feed. The experiments were conducted for 42 days using 45 chickens, each treatment consisted of 5 chickens as a replication. The variables measured include performance, carcass parameter, chemical composition of meat, physical quality of meat, the levels of malondialdehyde (MDA), cholesterol and fatty acid composition of meat. The experiment results showed that supplying black tea waste extract and energy â protein level significantly affected average daily gain, pH, cooking loss, MDA levels, saturated fatty acid (SFA), mono unsaturated fatty acid (MUFA) and poly unsaturated fatty acid (PUFA) of the meat (P<0,05). Supplying the black tea waste extract did not significantly affect performances, carcass production and chemical quality of the meat. It decreased meat pH significantly (P<0.05), levels of MDA and total of meat SFA (P<0,05). Black tea waste extract supply increased the total of MUFA and PUFA (P<0,05). Energy - protein level of ration did not make differences of chemical quality of meat, increased performances, carcass production, the water-holding capacity of meat, meat MDA levels, meat cholesterol, the total of MUFA and PUFA (P<0,05), however decreased meat SFA total (P<0,05). The results showed that the addition of black tea waste extracts as a feed additive has a good effect on the oxidation stability that is reflected in decreased levels of MDA and SFA total of meat and increased PUFA total in meat, without causing differences in meat quality. Level 500 mg/kg feed of tea waste extract combine with medium energy â protein feed level indicates the best result in performance, meat quality and oxidative stability.